2012
DOI: 10.1007/s10195-012-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined pubic rami and sacral osteoporotic fractures: a prospective study

Abstract: BackgroundPelvic osteoporotic fractures (POFs) are often associated with considerable morbidity and mortality mainly as a result of infections and cardiovascular events. Patients usually need prolonged institutionalization, rehabilitation, and follow-up, with a high rate of dependency and cost. The most common sites of POFs include the pubic rami, sacrum, ilium, and acetabulum. Combined pubic rami (PROFs) and sacral osteoporotic fractures (SOFs) have been reported, mostly in retrospective studies, describing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 23 publications
(70 reference statements)
3
56
0
3
Order By: Relevance
“…Mortality rates of osteoporotic pelvic fractures during hospitalization are high, similar to those seen for hip fractures: Marrinan et al [16 && ] reported an in-patient mortality rate of 9%, in agreement with Alnaib et al [17] who observed an in-hospital mortality rate of 10.5%. Within 3 months of fracture, mortality rate ranged from 7.1 to 13% [16 && ,18].…”
Section: Human Cost: Morbidity and Mortalitysupporting
confidence: 71%
See 1 more Smart Citation
“…Mortality rates of osteoporotic pelvic fractures during hospitalization are high, similar to those seen for hip fractures: Marrinan et al [16 && ] reported an in-patient mortality rate of 9%, in agreement with Alnaib et al [17] who observed an in-hospital mortality rate of 10.5%. Within 3 months of fracture, mortality rate ranged from 7.1 to 13% [16 && ,18].…”
Section: Human Cost: Morbidity and Mortalitysupporting
confidence: 71%
“…Also from this point of view, osteoporotic pelvic fractures are severe; in most studies, a large majority of patients admitted for pelvic fracture previously lived at home and were independent. However, at time to discharge nearly half of them have to go to a nursing home, community rehabilitation bed or required continuous bed care [10,17]. For example, in the study of Marrinan et al [16 && ], on admission to hospital, 89% of patients lived independently, but at the point of discharge from hospital, this figure dropped to 64% and the odds of changing from independent to institutionalized accommodation were significantly associated with age and length of hospital stay.…”
Section: Human Cost: Morbidity and Mortalitymentioning
confidence: 98%
“…This, upon reversion, means that more than 80% of patients with FFP had a posterior pelvic ring injury. It therefore is recommended that every patient with an FFP receives a pelvic CT-scan so that the severity of the injury is not underestimated (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…They are associated with high in-hospital mortality (104–14%5) and complication rates (20% to 50%6), as well as long average admission time (185 to 454 days). Many patients do not return to their premorbid independence 7.…”
Section: Discussionmentioning
confidence: 99%